Prevalence estimates of dementia in Colombia (2005-2020): transitions and stage of disease (2014)
Background: The only study involving a nationally representative sample to estimate dementia prevalence in Colombia has been the EPINEURO. This was a population-based survey of a stratified random sample of urban and rural residents of five regions of Colombia. The purpose of this paper was to estimate the number of people suffering from dementia and in particular Alzheimer's disease (AD) in Colombia by severity stage.